The Intuitionistic Fuzzy ELECTRE model. Issue 2 (3rd April 2018) - Rouyendegh, Babak Daneshvar
Abstract: The purpose of this research is to postulate and define a new model for Multi-Criteria Decision-Making (MCDM) problems utilizing the Intuitionistic Fuzzy ELimination Et Choix Traduisant la RÉalité (IFELECTRE) method, otherwise identified as the Intuitionistic Fuzzy Index of Hesitation Degree method. The Intuitionistic Fuzzy Sets (IFS) method offers certain advantages in using vagueness over a Fuzzy Set (FS): the IFELECTRE method is used to handle more complicated problems, whereas the Decision-Makers (DMs) have some vagueness in assigning option values to the objects considered. The processes of evaluating qualitative and quantitative scales are combined in this work and the proposed model enables different DMs to assess and use IFS. The original ELECTRE method cannot be operated effectively owing to a lack of precise information under different conditions.